Increased risk of atrial fibrillation in uterine fibroid patients: a nationwide population-based study - Seokmoon Han; Eue-Keun Choi; Hyo-Jeong Ahn; Soonil Kwon; Kyung-Do Han; So-Ryoung Lee; Seil Oh; Gregory Y. H. Lip (Scientific Reports)
Abstract The association between atrial fibrillation (AF) and uterine fibroids (UF) is unclear, though UF are linked to an elevated risk of cardiovascular disease. This study aimed to investigate the AF risk in UF patients. Females aged 20–39 who received health examinations from 2009 to 2012 were included. UF were defined using the ICD-10 codes, and surgical treatment status was defined by procedural codes. The primary outcome was incident AF, evaluated using a Cox regression model, which also assessed AF risk according to surgical treatment status. Among 2,574,349 participants (UF 20,682 [0.8%], mean age 29.8 ± 4.3 years, mean follow-up duration 7.3 ± 1.1 years), 3,868 patients developed AF (n = 61, UF; n = 3,807, control). AF incidence was higher in the UF group than the control (0.41 and 0.20 per 1,000 person-years, respectively). Multivariate Cox-regression analysis identified UF as an independent risk factor for AF (aHR 1.50, 95% CI 1.16–1.93, p = 0.002). Compared to the control group, UF group with surgery had similar AF risk (aHR 1.22, 95% CI 0.79–1.90), however, those without surgery had higher AF risk (aHR 1.69, 95% CI 1.24–2.30). UF patients were associated with increased risk of AF. Careful monitoring of arrhythmia development is warranted in women with UF.